Why Home-Schooling? Axiological Justifications for an Education Outside of the School System - Kucharska, Anna Maria (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
Since 1990 Poles have rediscovered home-schooling. Teaching and upbringing within the family is not a new concept – it preceded the development of institutionalised education and was strongly bonded with a social class and its needs. Nowadays, however rather unconsciously, some parents are coming back to a similar way of teaching at the same time wandering away from teaching at school with all its flaws. On the other hand home-schooling models are more often modern, Anglo-Saxon, where this form of teaching has many adherents.
Keywords: home-schooling; christian schools; values; upbringing environment